The hurricane heist [videorecording (DVD)] - Kebbell, Toby; Grace, Maggie, 1983-; Kwanten, Ryan, 1976- (Lionsgate, 2018)
As a massive hurricane builds, criminals infiltrate a U.S. Mint facility. Their plan: to steal $600 million and escape using a Category Five hurricane as cover. But a treasury agent and a storm chaser have a plan of their own, desperately racing against time, and the hurricane, to save the hostages and stop the thieves before their town is reduced to rubble.